Ovarian follicular dynamics in normal and repeat breeder cows - SHARMA, R K; RAWAL, C V S; HOQUE, M; ANSARI, M R; VARSHEN, V P (The Indian Journal of Animal Reproduction, 2007)
Follicular growth pattern was studied in nonnal and repeat breeder cross bred cows. Ultrasonic studies revealed that bovine oestrous cycle is characterized by two or three-wave of follicular growth commonly referred as anovulatory and ovulatory wave. The length of oestrous cycle was significantly higher (P < 0.01) in cows having three-wave of follicular growth compar’".d to those having two-wave of follicular growth. The study revealed that in two-wave cycle repeat breeder cows have altered pattern of follicular growth compared with nonnal cows. The maximum diameter of anovulatory dominant follicle was significantly higher (P < 0.05) in repeat breeder cows as compared to those in nonnal cows. Similarly, the ovulatory wave emerged earlier in repeat breeder cows (P < 0.05). The diameter of corpus luteum on day 8 of cycle was significantly smaller (P < 0:05) in repeat breeders compared to that in nonnal cows. However, progesterone concentrations did not differ significantly in nonnal and repeat breeder cows.